Pengaruh Pemahaman Hidup Kudus Menurut 1 Tesalonika 4:1-8 terhadap Perilaku Seksual Pemuda Remaja di GPdI Wilayah Sentani Timur Tengah - Priskila de Fretes; Zulkisar Pardede (Sekolah Tinggi Teologi Torsina Surakarta, 2020)
This study aimed to determine whether there is an influence of the under-standing of holy life according to 1 Thessalonians 4: 1-8 on the sexual behavior of GPdI youth/teenagers in the Sentani Timur Tengah Region; which dimensions affected the understanding of holy life according to 1 Thessalonians 4:1-8 on youth/ teenagers sexual behavior, and found out which background factors have the most influenced on sexual behavior in youth/teenagers in GPdI Sentani Timur Selatan Region. In this study, the population was youth/teenagers in the GPdI Sentani Timur Selatan Region totaling 123 people. This research used a quantitative (positivist) approach. The research method used was a quantitative research design with an explanatory-confirmatory method. Simple linear regression test results are Y = -47,727 + 0.864X. In conclusion, the understanding of the holy life according to 1 Thessalonians 4: 1-8 has a positive effect on the sexual behavior of GPdI youth/youth in Sentani Timur Selatan (Y), with the dimension of